SEPOTONG CERITA SIMBOLIS PRODUK CAKWE: ANTARA BRAND DAN JUGA DENDAM KESUMAT - Ichwan, ichwan Prastowo; Wibiyanto, Agung; Resmi, Prasiwi Citra (Sekolah Tinggi Pariwisata Sahid Surakarta, 2024)
The purpose of this article is to review a symbolic story behind the Cakwe product, exploring the connection between the brand and a deep-seated grudge. This traditional pastry, originally from China, has a long history, both symbolically and culturally, which is not widely known to the public. The research method used in this article is qualitative with descriptive analysis. The data utilized comes from references, including books and journals, which will be reduced and analyzed to form this writing. The result of this paper highlights the symbolism behind the Cakwe shape, which is long and made from two dough pieces, symbolizing the bodies of Prime Minister Qin Hui and his wife, who were blamed for the death of General Yue Fei. In terms of language connotation, both in Hokkien and Cantonese, or other Southern Chinese dialects, Cakwe can be interpreted as